PENGARUH PEMBERIAN JUS BUAH NAGA MERAH DAN BIJI CHIA TERHADAP KADAR KOLESTEROL TOTAL PENDERITA HIPERKOLESTEROLEMIA - Putri, Bernatara Aulia; Moviana, Yenny; Isdiany, Nitta; Saleky, Yohannes Willihelm (Jurnal Gizi dan Dietetik, 2023)
Hypercholesterolemia is the main cause of atherosclerosis. Dragon fruit juice and chia seeds is a product that rich in antioxidants, high in fiber, and a source of vitamin B and vitamin C so it can help reduce total cholesterol levels. The purpose of this study was to determine the effect of red dragon fruit juice and chia seeds on total cholesterol levels in hypercholesterolemic patients. This research design used a quasi-experimental two-group pre-post test. Samples were taken by purposive sampling of 32 samples which were divided into two groups. The intervention group was given 215 ml of red dragon fruit juice and chia seeds for 7 days and nutrition education, while the control group was given nutrition education. This research was conducted in February-March in the working area of the Pasirkaliki Health Center. The data collected included age, sex, medical history, education, occupation, weight, height, intake of fat, fiber and cholesterol, and total cholesterol levels. The results showed that there was a significant difference in the average cholesterol levels before and after the intervention group was given (p<0.05). In the control group there was no significant difference in the mean cholesterol levels before and after the intervention (p>0.05). There was a significant difference between the average total cholesterol level in the intervention group and the total cholesterol level in the control group (p<0.05) with an average reduction of 23.25 mg/dl. Samples are advised to consume red dragon fruit juice and chia seeds because these products are effective for lowering cholesterol levels.